Basic Materials Used in Removable Orthodontic Constructions in Children - Sanakhulov Jamshed Obloberdiyevich (Academia One Publishing, 2023)
The rapid development of modern orthodontic technology has led to the widespread introduction of previously unused structures of orthodontic devices made of various groups of restorative materials
Keywords: orthodontic technology; restorative materials